Empowering high school students’ banking literacy through QR Code-based Snakes and Ladders Game - Luciana Spica Almilia; Ellen Theresia Sihotang; Haekal Ridho Afandi; Dyana Purwandini; Ni Nyoman Asti Stya Putri (University of Merdeka Malang, 2025)
A 2024 national survey by the Financial Services Authority (FSA) revealed that 43% of Gen Z still lack an understanding of banking institutions. One high school facing similar challenges in banking education is SMA 17 Agustus 1945 (SMATAG) Surabaya. Student performance in the banking section of economics remains suboptimal, with average scores among 11th-grade social science students ranging from 6.0 to 6.2. Teachers currently lack interactive learning media to help students effectively grasp the material. To address this issue, the community service team from Hayam Wuruk Perbanas University implemented an interactive educational approach using a QR Code-based Snakes and Ladders game. The program employed a Community-Based Participatory Research (CBPR) method involving three economics teachers and 86 students. The stages included coordination, game board design and development, trials, further refinement, lectures and gameplay, and evaluation. The results showed a significant improvement in students’ banking knowledge, with average scores increasing from 42.70 (pre-test) to 86.14 (post-test). The overall program was well received, earning an average score of 4.07. These findings indicate that interactive, technology-based games can serve as effective educational tools and enhance students’ motivation to learn.